RELEVANSI SIKAP DAN MINAT MAHASISWA DENGAN KESIAPAN MENJADI GURU PROFESIONAL PADA JURUSAN PENDIDIKAN AGAMA ISLAM IAIN KEDIRI: SEBUAH ANALISIS MULTIPLE LINEAR REGRESSION - Muhammad Nabil Khasbulloh (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2018)
This research head for explaining behavior and interest of Islamic Education university student at IAIN Kediri as teacher aspirant toward their readiness becoming profesional teacher, and are teacher aspirant already have positive attitude toward teachership profession. In this research, what is meant by behavior and interest of teacher aspirant toward teachership profession is a tendency in responding about like or do not like they are toward teachership profession, which at last explained as behavior that related with the aspirant. This research use quantitative descriptive, ex-post facto method. The result of this research is university student have positive behavior and interest toward their readiness become profesional teacher. The research result are expected useful to prepare competency and activity of profesional teacher aspirants.